Exploring Taiwanese's smartphone user intention: an integrated model of technology acceptance model and information system successful model. (6th August 2019) - Cheng, Ching-Hsue; Chen, Chung-Hsi; Chen, You-Shyang; Guo, Ho-Long; Lin, Chien-Ku
The study is focused on behavioural intentions of smartphone users, and these are based on information system success model (ISSM) and technology acceptance model. In this study, we use SEM to examine the model that includes dimensions and relevant variables. The dimensions of model include information quality, system quality, service quality, perceived ease of use, perceived usefulness, attitude and behavioural intentions. The results indicate that there are no differences between perceived usefulness and information quality, system quality, and there is also no difference between perceived ease of use and behavioural intentions. In addition to above hypotheses the other are all supported among these hypotheses. We found the most indirect variable affect the behavioural intentions is system quality. This means that system quality is the most important factor to affect smartphone system. We also found that perceived ease of use is very important for smartphone users, and if the smartphone systems are not easy to use, they would not be accepted by people.